Concrete evidence: outplanted corals for reef restoration do not need extended curing of ordinary Portland cement - E. G. Knoester; A. Vos; C. Saru; A. J. Murk; R. Osinga (Royal Society Open Science, 2024)
Artificial reefs for coral reef restoration are often concrete-based. After concrete is poured, it initially has a high surface pH (approx. 13), which neutralizes within several weeks. During this curing, colonization by marine microalgae is delayed and also macrobenthos such as corals may be impacted. In this study, we evaluated how concrete curing time applied prior to the deployment of artificial reefs affected coral performance. Fragments of five coral species were outplanted onto ordinary Portland concrete discs (n = 10) that had been cured on land. Seven different curing periods were applied, ranging from one day up to four months. The discs with corals were deployed at a Kenyan reef and photographed at the start and end of the experiment. After 1 year, coral cover had increased for four coral species and declined for one, but this was unrelated to concrete curing time. Also, no effect of curing time was seen on the development of other common benthic organisms such as macroalgae or soft corals. We conclude that curing of concrete is unlikely to have any long-term negative impacts on coral performance and therefore, extended curing of artificial reefs prior to coral attachment is unlikely to benefit reef restoration efforts.